Inter-university cooperation between France and Bosnia and Herzegovina: Student mobility and the role of the French education system in strengthening higher education in Bosnia and Herzegovina - Lazić Nikola; Perišić Nikola (Srpska Politička Misao)
Higher education plays a key role in the development of a country and society. Cooperation between different universities and educational institutions at the international level is important for enriching the educational experience of students, sharing knowledge and innovation, and promoting cultural diversity. This scientific paper examines the scope of the influence of the French Republic and its educational model on the development of higher education in the Federation of Bosnia and Herzegovina. The specificity of Bosnia and Herzegovina is reflected in the multiculturalism that dominates, but also in the fact that this country has been constituting itself for the last few decades. In order to represent the interests and needs of different groups in the most successful ways, Bosnia and Herzegovina applied the existing examples of good practice from France in various social spheres, among others in the field of education. The French education system is one of the world's most successful higher education systems. In addition, the French state, through various incentives such as donations or scholarships to the best students, influenced the development and institutionalization of universities around the world. The basic hypothesis on which this work is based is that inter-university cooperation between France and Bosnia and Herzegovina contributes to the improvement of the quality of higher education, especially in terms of academic excellence and research capacities of Bosnia and Herzegovina. The method on the basis of which the hypothesis is tested is the method of technology and knowledge transfer techniques, and the comparative method will be used as an additional method.